Sacred buildings : a design manual - Stegers, Rudolf (Design Manuals., 2008)
The building of religious structures represents a rare opportunity for the architect to concentrate on the creation of volume, space, and form. Sacred architecture is far less determined than other building tasks by functional requirements, norms, and standards. As a rule, it is free to unfold as pure architecture. Thus in design terms this building task offers enormous freedoms to the architect. At the same time, however, the special atmospherics of sacred spaces call, on the part of the architect, for a highly sensitive treatment of religion and the relevant cultural and architectural tradit.